Serat Cabolek, Sufism Book or Ideology Documents of Javanese Priyayi? - Fauzan, Pepen Irpan; Fata, Ahmad Khoirul (UIN Maulana Malik Ibrahim Malang, 2018)
Many researches concern with the dialectic between Islam and tradition of Java. One of them is Soebardi studying Serat Cabolek, a manuscript that illustrated the dialectic between Islam and Javanese tradition in 18/19th century. Through philological studies Soebardi has produced a PhD thesis at The Australia National University (1967), and published in 1975 under title “The Book of Cabolek”. This book should be appreciated for having presented an important study on Islam and Java. Yet, it also needs to be studied more deeply through historical studies in order to obtain clearer information about the context. This article attempts to give a short review about the content of the book, and gives a critical explanation based on its socio-historical perspective. The result is that the story in Serat Cabolek is a construction of Javanese Priyayi on their history. It is an upscale historical document, to strengthen the king’s position as Panatagama. Dialektika Islam dan tradisi Jawa menarik perhatian banyak peneliti. Salah satunya adalah Soebardi yang mengkaji Serat Cebolek, sebuah naskah yang dianggap menjadi gambaran dialektika Islam-Jawa abad 18/19 M. Melalui kajian filologis Soebardi menghasilkan karya disertasi di Australia National University tahun 1967, dan diterbitkan dengan judul “The Book of Cabolek” pada 1975. Buku ini patut diapresiasi karena telah menyajikan satu teks yang penting bagi studi Islam dan Jawa. Namun juga perlu ditelaah melalui penelusuran sejarah untuk memahami konteksnya agar informasi yang didapat lebih lengkap. Tulisan ini berusaha memberikan ikhtisar tehadap isi buku tersebut dengan disertai penjelasan kritis berdasarkan perspektif sosio-historisnya. Hasil kajian menunjukkan bahwa kisah yang terdapat dalam Serat Cebolek merupakan konstruksi priyayi mengenai realitas sejarah. Serat ini adalah dokumen sejarah sosial kelas atas, sebagai simbol peneguhan kepentingan raja sebagai panatagama.